Peran Perawat dalam Manajemen Stroke Berbasis Bukti: Suatu Tinjauan Literatur - Nurfianti, Arina (Tanjungpura Journal of Nursing Practice and Education, 2025)
The incidence of stroke continues to increase globally, requiring the involvement of a multidisciplinary team to achieve optimal clinical outcomes. Within this collaboration, nurses play a central role throughout all stages of stroke care. This study aims to present a series of current evidence-based practices in stroke management from a multidisciplinary perspective, with particular emphasis on the role and contribution of nurses. This article serves as a reference for the current development of nursing care for stroke patients. This review article outlines recent evidence-based approaches in stroke management, focusing on the role of nurses and nursing practices across the continuum of care. The review summarizes nursing practices from the pre-hospital stage to rehabilitation, including acute interventions, clinical assessments, and nurses’ roles in detecting complications and supporting patient recovery. This review underscores the importance of interprofessional collaboration and the application of guideline-based nursing practices to improve stroke outcomes. It also highlights the expanding role of nurses in supporting comprehensive stroke management.